O drama social, o herói trágico e o "sonho americano" em a morte de um caixeiro-viajante de Arthur Miller - Poppelaars, Antonius Gerardus Maria (2016)
Willy Loman, the protagonist of Arthur Miller’s Death of a Salesman (1949) is a simple, flawed, middle class salesman. Can a common man such as Willy Loman be considered as a tragic hero? Does tragedy still exist in modern drama? Could the dark side of the “American dream” be the external flaw that provoces Loman’s fall? The objective of studying Arthur Miller’s play Death of a Salesman is focused on the possibility whether the protagonist, Willy Loman, can be considered a tragic hero. This study consists of a literary and historical perspective and is of a qualitative-descriptive character. The problem focuses on the question: what could be the influence, or rather, the illusion of the “American dream” that causes Willy’s tragic fall? This study is constructed by three cornerstones: first, the analysis of drama and tragedy from the perspective of Aristotle’s theory; second, the analysis of social drama and ultimately, the historical and literary perspective of the concept of the “American dream” as a reason for Willy Loman’s fall. The results of this study indicate that Death of a Salesman is not a period piece and that this play highlights issues from the past that are still current. It is noticed that Willy Loman meets his inglorious end because he is fooled and deluded by the “American dream”. The development of tragedy, culminating in modern social drama, indicates that a common man can be tragic, exactly because of the fact that Willy is an ordinary human being, which even more provoces feelings such as fear and pity, once what happened to him can happen to anyone of us.